2018
DOI: 10.1002/ajmg.a.38592
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐allelic mutations of CCDC88C are a rare cause of severe congenital hydrocephalus

Abstract: Congenital or infantile hydrocephalus is caused by genetic and non-genetic factors and is highly heterogeneous in etiology. In recent studies, a limited number of genetic causes of hydrocephalus have been identified. To date, recessive mutations in the CCDC88C gene have been identified as a cause of non-syndromic congenital hydrocephalus in three reported families. Here, we report the fourth known family with two affected individuals with congenital hydrocephalus due to a homozygous mutation in the CCDC88C gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Hydrocephalus, a common birth defect with an estimated incidence of 1:1000 (1), is characterized by enlarged intracerebral ventricles. It causes convulsions, mental disability, and even death in patients (2).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocephalus, a common birth defect with an estimated incidence of 1:1000 (1), is characterized by enlarged intracerebral ventricles. It causes convulsions, mental disability, and even death in patients (2).…”
Section: Introductionmentioning
confidence: 99%
“…Despite abundant information on the biochemical and signaling mechanisms of this growing family of regulators, direct in vivo evidence for a physiological process controlled by them is still lacking. We reasoned that DAPLE, a recently identified member of this group of GEFs, might serve as a G protein activator during embryonic morphogenesis based on the observation that congenital mutations in this gene cause neurodevelopmental disorders in humans (Ekici et al, 2010; Drielsma et al, 2012; Ruggeri et al, 2018; Wallis et al, 2018; Zwaveling-Soonawala et al, 2018; e.g., nonsyndromic hydrocephalus). Here, we show that DAPLE is a tissue-specific activator of G proteins that triggers a signaling cascade culminating in the apical constriction of neuroepithelial cells during neurulation.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest monogenic link of hydrocephalus had been made to L1CAM (Rosenthal et al , ; Jouet et al , ; Van Camp et al , ; Coucke et al , ), which encodes the L1 neuronal cell adhesion molecule. Subsequent studies identified AP1S2 , a gene of subunit 2 of clathrin‐associated adaptor protein complex 1 (Saillour et al , ; Cacciagli et al , ), and CCDC88C , which encodes DAPLE, a protein involved in Wnt signaling (Ekici et al , ; Drielsma et al , ; Ruggeri et al , ). A more recent gene linked to congenital hydrocephalus is MPDZ , encoding a large modular scaffold protein that consists of 13 PDZ domains and one L27 domain (Ullmer et al , ; Adachi et al , ).…”
Section: Introductionmentioning
confidence: 99%